Konservasi Budaya Udar Gelung dan Eksistensinya dalam Peradaban Modern (Studi Desa Mojorejo, Kebonsari, Madiun) - Muchlis Daroini; Kayyis Fithri Ajhuri; Moh. Mujibur Rohman (Journal of Education and Culture, 2025)
Tradition is a social fact as well as a medium to see how far social development has occurred. Tradition creates a social structure to be part of the mechanism of change in every social development. As a part of culture, tradition becomes a space for expression of group attachment to supernatural powers. However, as a subsystem of the social mechanism, tradition will always experience re-construction or even disposal from the form of social selection. Religion, politics, economy and culture move forward towards change, tradition will become a milestone for the birth of a new culture as a form of dialectical process between social elements. However, the substance of a tradition as well as religion will actually give birth to a very high source of culture. Likewise with Udar Gelung, a tradition that has disappeared but its existence remains in Mojorejo Village. With a qualitative descriptive method, this study aims to reveal the forms of change in the Udar Gelung tradition in Mojorejo Village, Madiun Regency, East Java. With a social change approach, it was discovered how the Udar Gelung Tradition became a communication system for the Mojorejo Village government in planning development democratically by involving all elements of society with the spirit of Udar Gelung.